Biological properties of swine vesicular disease virus strain 2348 Italy/2008 - Ye. N. Kalinina; S. N. Fomina (Ветеринария сегодня)
Swine vesicular disease (SVD) is a viral infectious disease, which, if acute, is manifested by the clinical pattern similar to a number of vesicular diseases including foot-and-mouth disease. In case of subclinical disease, there are no evident clinical signs, therefore the diagnosis is problematic, and there can be the risk of the disease introduction into the Russian Federation with the infected pigs. The key measure for the prevention of SVD introduction involves control diagnostic testing of all animals imported in the country that makes it necessary to keep updated the currently used methods and tools for the disease laboratory diagnosis. The paper demonstrates data on experimental infection of pigs with SVDV strain 2348 Italy/2008 that belongs to the most recent one of the four known phylogenetic groups. The virus was kindly provided by the World Reference Laboratory for Foot-and-Mouth Disease (Pirbright, Great Britain), and it was adapted to the monolayer continuous cell cultures of porcine origin (IB-RS-2 and PGSK-30). The pigs were intradermally infected with concentrated cultured virus at a dose of 109 TCID50. The infected animals demonstrated clinical signs typical for the acute disease. There was evidence that the virus was not transmitted to the intact animal in case husbandry conditions were met that allowed to avoid the infection transmission by the fecal-oral and contact mechanisms. As a result of the experiment, reference sera were collected at different time intervals post infection and their activity was determined using virus microneutralization test in cell culture and ELISA. Aphthae collected from the infected animals were deposited into the Strain collection of the Reference Laboratory for Foot-and-Mouth Disease, FGBI “ARRIAH”.